Critical issues in organization development : case studies for analysis and discussion - Johnson, Homer H.; Sorensen, Peter F.; Yaeger, Therese F. (Contemporary trends in organization development and change., 2013)
This case study book provides 30 cases and responses from 90 OD consultants with expert insights specific to each particular case topic. This book is the culmination of ten years of collaboration between the Homer Johnson, Peter Sorensen and Therese Yaeger, and the OD Network that originally printed these cases in the OD Practitioner. Now with the 30 case studies compiled in one OD resource book, both practitioners and academics can experience an OD challenge and value the differing responses from OD experts.